Incidence of parasitoids and predators on eggs of seven species of Therididae (Araneae) - Triana Cambronero, Emilia (2012)
Although many characteristics of the egg sacs of spiders likely evolved to reduce the effect of parasites and predators that attack their eggs, many parasite and predator insects have become specialized on spider eggs. Eggs of six of the seven species of Theridiidae included in this study were attacked by wasp parasites (Baeus achaearaneus, Idris sp., and Comastichus zopheros), and two by the specialized spider egg predator (Neuroptera: Zeugomantispa minuta). The incidence of parasites in the egg sacs varied across species. Parasites attacked more than 60% of the egg sacs of Tidarren sisyphoides and Parasteatoda tepidariorum, but none of the sacs of Latrodectus geometricus. The incidence of parasites in the egg sacs was higher during the dry season for T. sisyphoides, and during the rainy season for P. tepidariorum. The proportion of the eggs parasitized per egg sac varied from 0.09 (± 0.19) in Nesticodes rufipes to 0.50 (± 0.46) in T. sisyphoides. Differences in the biology of parasites, as well as in the structure of spider webs and hábitat preference of spiders, may influence the incidence of parasitism and proportion of eggs parasitized in each egg sac.